The Private College Public Relations Management: A Case Study - Soim Soim; Nik Haryanti; Nilam Nurohmah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This article aims to analyze public relations strategies in improving the quality of education, public relations strategies in improving the image of education, and information management carried out by a private university in East Java. A qualitative descriptive approach is carried out with a case study at IAI Pangeran Diponegoro Nganjuk. Research data was obtained through interviews, observation, and documentation. The results found that public relations at the university did not have a specific organizational structure, but everyone acted as public relations and carried out the function of public relations; the programs those public relations have launched must be implemented to improve the quality of education that refers to the standard process and educational outcomes. The public relations strategy is determined to improve the image through regular program procurement, collaboration with the government, mass media, figures who have mass, other institutions, providing scholarships, and community service. It uses a vertical, horizontal, and diagonal communication system to communicate with the internal public, while the external public uses a two-way communication system.